Model of Profit Maximization of The Giant Gourami (Osphronemus goramy) Culture - Dian Wijayanto; Faik Kurohman; Ristiawan Nugroho (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
The research purpose was to develop a model of profit maximization that can be applied to the giant gourami culture. The development of fish growth model used polynomial growth function. Profit maximization process used the first derivative of profit equation to culture time equal to zero. This research also developed the equations to estimate the culture time to reach the size target of fish. The research has been proven that this research model could be applied in the giant gouramy culture. In the case of this study, the giant gouramy culture can achieve the maximum profit at 324 days and the profit of IDR. 7 847 700 per culture cycle. If we used a size target 500 g, the culture of the giant gouramy need 135 days of culture time.